2016
DOI: 10.5897/ajar2015.9712
|View full text |Cite
|
Sign up to set email alerts
|

Physical and physicochemical composition of mangaba fruits (Hancornia speciosa Gomes) at three maturity stages

Abstract: The mangaba (Hancornia speciosa Gomes) is a typical fruit of the Brazilian cerrado and caatinga. It has excellent nutritional composition but there are no studies reporting the fruit characteristics and its industrial use. The aim of this study was to analyze the physical and physicochemical characteristics of mangaba fruit in three different maturity stages. Fruit weight, volume, length, titratable acidity, vitamin C, soluble solids and color at 1/3 ripe, 2/3 ripe and ripe maturity stages were analyzed. Physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
1
1
Order By: Relevance
“…This is an important quality attribute to be considered in conservation and improvement programs. The obtained means were higher than those from Plácido et al (2016) study, which was 188.33 mg 100g -1 , when evaluating mangaba fruit at three maturation stages. The most significant values observed in the present study were consistent with those of Silva et al (2012), when they characterized fruits of natural populations from the State of Sergipe.…”
Section: Resultscontrasting
confidence: 76%
“…This is an important quality attribute to be considered in conservation and improvement programs. The obtained means were higher than those from Plácido et al (2016) study, which was 188.33 mg 100g -1 , when evaluating mangaba fruit at three maturation stages. The most significant values observed in the present study were consistent with those of Silva et al (2012), when they characterized fruits of natural populations from the State of Sergipe.…”
Section: Resultscontrasting
confidence: 76%
“…The results related soluble solids (SS) on average of 19%, SS / TA ratio of 11.18, and a high content of ascorbic acid, being these data higher than those reported by Plácido et al (2016), mainly for ascorbic acid (AA), but in the range reported by Carnelossi et al (2009) and Santos et al (2009), for similar maturity stage.…”
Section: Discussionmentioning
confidence: 51%